A Semi-Automatic Data Management Framework for Studying Thermal Comfort, Cognitive Performance, Physiological Performance, and Environmental Parameters in Semi-Outdoor Spaces - Chen, Shisheng (MDPI AG, 2023)
10.3390/su15010183